2014
DOI: 10.1186/1471-2458-14-85
|View full text |Cite
|
Sign up to set email alerts
|

Victimization of Peruvian adolescents and health risk behaviors: young lives cohort

Abstract: BackgroundWhile extensive research has been conducted on bullying and victimization in western countries, research is lacking in low- and middle-income settings. This study focused on bullying victimization in Peru. It explored the relationship between the caregiver’s perception of child victimization and the child’s view of selected negative experiences occurring with other children their age. Also, the study examined the association between victimization and adolescent health risk behaviors.MethodsThis study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 37 publications
0
16
1
Order By: Relevance
“…The cross‐sectional analysis cannot offer insights in causation, and there is always the possibility that individuals who engage more in health risk behaviors have a higher possibility of being involved in bullying and cyberbullying incidents. However, although the reciprocal relationship of bullying with health risk behaviors is very plausible (Maniglio, ), longitudinal research suggests that after adjustment for possible confounding variables, bullying is independently associated with health risk behaviors (Crookston et al., ).…”
Section: Limitationsmentioning
confidence: 99%
“…The cross‐sectional analysis cannot offer insights in causation, and there is always the possibility that individuals who engage more in health risk behaviors have a higher possibility of being involved in bullying and cyberbullying incidents. However, although the reciprocal relationship of bullying with health risk behaviors is very plausible (Maniglio, ), longitudinal research suggests that after adjustment for possible confounding variables, bullying is independently associated with health risk behaviors (Crookston et al., ).…”
Section: Limitationsmentioning
confidence: 99%
“…Results from these studies have highlighted on the importance of promoting a safe and bully-free learning environment for better educational development of students. Some research also revealed that victimization is related to the use of harmful substances like cigarette, tobacco, alcohol [18][19][20] as well as involvement in sexual risk behavior [21] and physical fight [22,23]. There is emerging evidence around association of bullying on body image.…”
Section: Introductionmentioning
confidence: 99%
“…Using Young Lives data, Crookston et al (2014) found that children who were bullied at ages 8 and 15 were at a higher risk of engaging in risk behaviours, including smoking cigarettes, drinking alcohol and sexual relationships.…”
Section: Data and Evidencementioning
confidence: 99%